Pengaruh Keterlibatan Mahasiswa KKN Universitas Muslim Nusantara Al Washliyah terhadap Partisipasi Masyarakat dalam Konservasi Mangrove di Desa Karang Gading - Risnawaty, Risnawaty; Yeltriana, Yeltriana; Nurhaliza, Siti; Nabila, Talitha; Husna, Laila Diyatul; Nadila, Siska (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The mangrove ecosystem is an ecosystem that is located in a coastal area that is affected by the flooding of the sea so that the soil is always filled water. The study aims to examine the influence of student involvement on community participation in mangrove conservation in the Gading coral village. Public participation in conservation activities is crucial to the sustainability of such efforts. This research point uses a qualitative approach to understanding in depth the influence of student KKN UMNAW involvement on the participation of the public in mangrove conservation in the Gading coral village. The result of this study indicate that students KKN UMNAW involvement contributes positively to increased public in the Gading coral Village.